Vibrational and Normal Coordinate Analysis of 2-Mercaptobenzothiazole - Krishnakumar, V.; Ramaswamy, R.; Natarajan, A. (Asian Journal of Chemistry, 2010)
The FTIR and FT Raman spectra of 2-mercaptobenzothiazole have been recorded and the normal coordinate analysis has been carried out by assuming Cs point group symmetry. The 39 fundamental modes of vibrations are assigned based on the PED calculations.